PENGARUH BUDAYA ORGANISASI, MOTIVASI DAN PROFESIONALISME TERHADAP KINERJA AUDITOR INTERNAL (Survey pada BUMN Sektor Jasa Keuangan & Asuransi di Kota Bandung) - Ruslina Lisda; Sukesih Sukesih (Universitas Logistik dan Bisnis Internasional, 2020)
This study aims to examine and analyze how much influence Organizational Culture, Motivation and Professionalism to the Performance of Internal Auditors. Population in this research is Internal Auditor and Internal Supervision Unit in the State Industry Companies financial and insurance services in Bandung City. The number of seals taken as many as 46 respondents. The research method used is descriptive and verification method. Data collection techniques are done through primary data with questionnaires. Sampling technique using Probability Sampling technique using Simple Random Sampling method. Statistical analysis used in this research are validity test, reliability test, multiple correlation analysis, multiple regression analysis, T test, F test, and coefficient of determination. Simultaneously shows that the magnitude of the influence of organizational culture, motivation and professionalism to the performance of internal auditors of 70,7%, while the rest of 20,3% influenced by other factor not observed in this research. Thus, the higher the organizational culture, motivation and professionalism will further improve the performance of internal auditors.